Optically enhanced charge transfer between C60 and single-wall carbon nanotubes in hybrid electronic devices. - Allen, C; Liu, G; Chen, Y; Robertson, A; He, K; Porfyrakis, K; Zhang, J; Briggs, G; Warner, J (2014)
In this article we probe the nature of electronic interactions between the components of hybrid C60-carbon nanotube structures. Utilizing an aromatic mediator we selectively attach C60 molecules to carbon nanotube field-effect transistor devices. Structural characterization via atomic force and transmission electron microscopy confirm the selectivity of this attachment. Charge transfer from the carbon nanotube to the C60 molecules is evidenced by a blue shift of the Raman G(+) peak position and increased threshold voltage of the transistor transfer characteristics. We estimate this charge transfer to increase the device density of holes per unit length by up to 0.85 nm(-1) and demonstrate further optically enhanced charge transfer which increases the hole density by an additional 0.16 nm(-1).